In vitro and In vivo Evaluation of Chitosan/Karaya Gum Interpolymer Complex Based Mucoadhesive Buccal Films of Tramadol HCl - Patel, Adil (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: The main objective of the study was to assess the potential application of Chitosan/Karaya gum interpolymer complex to develop the novel rate controlled buccal mucoadhesive drug delivery system. Developed drug delivery system is capable to administer opioid analgesic drug tramadol HCl directly into systemic circulation via buccal mucosa. The developed drug delivery system would be more effective in terms of improving bioavailability, quick onset of action and reduction in dose related side effects of drugs which are suffering from hepatic first pass metabolism. Materials and Methods: Chitosan and karaya gum were selected for the preparation of interpolymer complex. Resulted interpolymer complex was characterized by Fourier-transform infrared and scanning electron microscopy. Further, the swelling behaviour of interpolymer complex was studied compare to karaya gum alone. Mucoadhesive bilayered buccal films were prepared from Interpolymer complexes by solvent casting method. An impermeable ethyl cellulose backing layer was placed to ensure unidirectional drug release from filmes. The resulted mucoadhesive buccal films were evaluated for swelling index, folding endurance, bioadhesive strength, ex vivo diffusion of the drug, in vitro dissolution and in vivo absorption of the drug. An opioid analgesic Tramadol HCl was used to study the nature of drug release from buccal films. A software aided optimization was carried out to understand the effect of formulation factors like amount of inter polymer complex and plasticizer at three different levels on three major properties of films like swelling index, tensile strength and in vitro dissolution. Result and Discussion: It has been observed that all resultant buccal films prepared by using inter polymer complex between Karaya gum and chitosan have shown good structural integrity, good mucoadhesive strength, satisfactory drug release and are capable to improve the in vivo absorption as well as plasma residence time.